Implementation and Evaluation of Teachers’ Performance Supervision at Madrasah Aliyah (Islamic Senior High School) - Tambrin, Muhammad; Wasliman, Iim; Hanafiah, Hanafiah; Mudrikah, Achmad (LPPM Undiksha, 2021)
Observing the quality of education should include teachers as the frontline in education. Even a good curriculum and program will be meaningless if the teacher does not implement it responsibly and consistently. This study aims to analyze teacher performance supervision programs, organize teacher performance supervision programs, movement and leadership supervision of teacher performance, control the effectiveness of teacher performance supervision, and creative and innovative ideas in realizing the effectiveness of teacher performance supervision. This research uses a qualitative approach with the Case Study method. The method used to collect data is interviews, observation, and documentation. The instrument used to collect data is a questionnaire. Research subjects or research respondents were selected purposively. The technique used to analyze the data is descriptive qualitative analysis. The results of this study are, first, the planning program has not been implemented effectively due to the problem of limited resources. Second, the implementation of supervision has not been carried out optimally. Third, the movement and leadership went relatively well; however, improvements are still needed in the managerial aspects of leadership. Fourth, controlling the effectiveness of teacher performance supervision is carried out in stages. Fifth, creative and innovative ideas emphasize strengthening supervision of teacher performance in Madrasah Aliyah education units and e-Kinerja applications. In addition, the implementation and evaluation of teacher performance supervision have been carried out by the Standard Operating Procedures (SOP) issued by the Ministry of Religion of the Republic of Indonesia. However, the results are still not practical due to various resource constraints.